2003
DOI: 10.3766/jaaa.14.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity and Reliability of Adult Hearing Screening Techniques

Abstract: The purpose of this study was to evaluate and compare the efficacy of hearing screening tools to identify hearing loss in the older adult population. The test-retest reliability of both the AuDX DPOAE hand-held screener and subjective otoscopic ratings of percent earwax accumulation were evaluated. Additionally, the predictive validity was investigated for five hearing screening tools: the DPOAE hand-held screener, pure-tone screening, screening otoscopy, self-assessment of communication, and case history scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…One also complained that during the behavioral screening, the earphones were too tight and frequently tried to adjust them. It is possible that either their extraneous movement generated enough noise to mask the pure‐tone stimuli, the DPOAEs were not sensitive enough to their level of hearing loss [Gorga et al, 1997] or that pure‐tone threshold screening may have a greater predictive validity for SNHL [Scudder et al, 2003].…”
Section: Resultsmentioning
confidence: 99%
“…One also complained that during the behavioral screening, the earphones were too tight and frequently tried to adjust them. It is possible that either their extraneous movement generated enough noise to mask the pure‐tone stimuli, the DPOAEs were not sensitive enough to their level of hearing loss [Gorga et al, 1997] or that pure‐tone threshold screening may have a greater predictive validity for SNHL [Scudder et al, 2003].…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis and early intervention, as well as the implementation of a hearing reeducation program specific to the population of adults and older adults, are key issues to improve quality of life for this population and, consequently, enable them to enjoy a better family life and social integration. 3 4 8 17 18 19 In presbycusis, however, as the hearing loss occurs gradually and progresses slowly, 4 20 21 and it often goes unnoticed or is denied by individuals during its early stage. 3 11 Therefore, hearing screening should be a standard procedure in hospitals, health centers, and clinics, with the aim of quickly, easily, and inexpensively testing a large number of individuals, thus enabling early diagnosis and treatment and decreasing the consequences of hearing deprivation.…”
Section: Introductionmentioning
confidence: 99%
“… 3 11 Therefore, hearing screening should be a standard procedure in hospitals, health centers, and clinics, with the aim of quickly, easily, and inexpensively testing a large number of individuals, thus enabling early diagnosis and treatment and decreasing the consequences of hearing deprivation. 5 10 17 18 20 22 This procedure, however, is still not commonly used by professionals working with adults and older adults. 23 In Brazil, the most commonly used method to detect hearing loss is the complete audiometric evaluation, which requires a soundproof booth, and thus it is not accessible as a screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have found that DPOAEs have a high reliability as well (Parthasarathy & Klostermann, 2001). DPOAEs have been found to be reliable for the pass/fail needed in a screening hearing test; however, they are not considered valid for a true measure of hearing loss in adults (Scudder, Culbertson, Waldron, & Stewart, 2003).…”
Section: Methodsmentioning
confidence: 99%